Semantic Dementia Shows both Storage and Access Disorders of Semantic Memory - Yumi Takahashi; Kenichi Meguro; Masahiro Nakatsuka; Mari Kasai; Kyoko Akanuma; Satoshi Yamaguchi (Behavioural Neurology)
Objective. Previous studies have shown that some patients with semantic dementia (SD) have memory storage disorders, while others have access disorders. Here, we report three SD cases with both disorders. Methods. Ten pictures and ten words were prepared as visual stimuli to determine if the patients could correctly answer names and select pictures after hearing the names of items (Card Presentation Task, assessing memory storage disorder). In a second task, the viewing time was set at 20 or 300 msec (Momentary Presentation Task, evaluating memory access disorder) using items for which correct answers were given in the first task. The results were compared with those for 6 patients with Alzheimer’s disease (AD). Results. The SD patients had lower scores than the AD group for both tasks, suggesting both storage and access disorders. The AD group had almost perfect scores on the Card Presentation Task but showed impairment on the Momentary Presentation Task, although to a lesser extent than the SD cases. Conclusions. These results suggest that SD patients have both storage and access disorders and have more severe access disorder than patients with AD.